2017
DOI: 10.1055/s-0043-120198
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theoretical Analysis, In Silico Modeling, Synthesis, Anti-Microbial and Anti-TB Evaluation of Novel Quinoxaline Derivatives

Abstract: A number of analogs found markedly potent anti-microbial and anti-TB activity. The relationship between the functional group variation and the biological activity of the evaluated compounds were well discussed. The observed study report was showing that the compound S6: (4-nitro substitution) exhibited most potent effective anti-microbial and anti-TB activity out of various tested compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Herein all the synthesized compounds were investigated for in vitro anti-tubercular activity wherein results showed that compound 147 was sensitive at 1.95 μg/mL concentration and showed good activity. [78] Srinivasarao et al, developed some 1,2,3-triazole based quinoxaline as potential anti-tubercular agents (148, Figure 44). .…”
Section: Anti-tubercular Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Herein all the synthesized compounds were investigated for in vitro anti-tubercular activity wherein results showed that compound 147 was sensitive at 1.95 μg/mL concentration and showed good activity. [78] Srinivasarao et al, developed some 1,2,3-triazole based quinoxaline as potential anti-tubercular agents (148, Figure 44). .…”
Section: Anti-tubercular Activitymentioning
confidence: 99%
“…Compound 147 also showed good activity with MIC value of 7.81 μg/mL when compared with standard drug ciprofloxacin (MIC=7.81 μg/mL) and ketoconazole (MIC: 7.81 μg/mL). Herein all the synthesized compounds were investigated for in vitro anti‐tubercular activity wherein results showed that compound 147 was sensitive at 1.95 μg/mL concentration and showed good activity [78] …”
Section: Pharmacological Activities Of Quinoxaline‐based Compoundsmentioning
confidence: 99%
“…Kyoto encyclopedia of genes and genomes database was utilized for the study of graph theoretical analysis. The influential proteins was recognized and chosen by network of protein interaction (mtu: 00770) in homo sapiens [25][26][27][28].…”
Section: Graph Theoretical Analysismentioning
confidence: 99%
“…A large number of pyrimidine and their derivatives are reported to possess a wide range of biological activities such as anticancer (Ahmed et al, 2009) , anxiolytic (Popik et al, 2006) , and antimicrobial (Selvam and Kumar,10 b,a) . Moreover, the pyrimidine derivatives are used as inhibitors of kinases, mainly to inhibit mediating signals of mitogenic and other events of cellular activities (Saravanan et al, 2018;Selvam et al, 12 b) such as differentiation, cell proliferation, migration, metabolism, and immune response. Also, many of the observed data indicate that these derivatives might block the proliferation of various cancer cell lines (Kamal et al, 2013;Prabhu et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%